Comparison of antigen-specific I-region-associated cell interaction factors. - Feldmann, M; Erb, P; Kontiainen, S; Todd, I; Woody, J (1979)
Two basic types of factors reacting with anti-I region (anti-Ia) antisera are compared, those derived from macrophage-like antigen presenting cells and others derived from T-lymphocytes, of either the suppressor or helper type. Despite the common property of reacting with anti-Ia antisera, the two sets of factors differ by many criteria. Macrophages, upon culture with antigen, release complexes of Ia antigen and a fragment of the original immunogen. This material is only produced by responder macrophages and thus appears to be a soluble Ir gene product. The genetic restriction of the T-macrophage interaction was investigated in chimeras, and it was found that the host environment as well as the donor genotype was of importance in determining restrictions, which were thus not really directed to "self." There was no evidence for intrinsic T-cell Ir genes, as nonresponder stem cells developed into responder T-cells in a (responder X nonresponder) F1 environment. However, these cells only responded in the presence of responder macrophages. Specific T-cell factors are different in nature. These all react with anti-Ia antisera, but the nature or function of the T-cell Ia is unknown. The basic structure involves a VARIAble region" responsible for antigen binding which, as it reacts with anti-idiotype antisera and anti-variable region framework antisera is an immunoglobulin variable region. There is also a "constant region," defined by its biological properties as well as by specific rabbit antisera. This two-region nature of specific factors is reminiscent of immunoglobulin structure and it is a reasonable hypothesis that the constant region is linked to the Ig cluster of genes.